PROMOTION TRAINING THROUGH SOCIAL MEDIA and KRETEK MACHINES FOR FLOWER HOUSE UMKM IN BANYURIP VILLAGE, KEDAMAIAN DISTRICT, GRESIK REGENCY - Estik Hari Prastiwi; M Sihab Ridwan; Sariah; Julia Wulandari (International Conference of Innovation and Community Engagement, 2025)
Community service is carried out for flower farmers in Banyu Urip Village, Kedamaian District, Gresik Regency. Mr. Faisal, one of the flower farmers in Banyu Urip Village, has a business making gardens and selling large trees. The problem faced by Mr. Faisal is not having a kretek machine that functions to transport large trees from Mr. Faisal’s flower stand location to the buyer’s place or the garden made by Mr. Faisal. The PKM method provided is to provide Ttg tools, namely kretek machines and provide training and promotional assistance via social media so that Mr. Faisal’s garden making services are better known to consumers. Assistance is provided to Mr. Faisal so that he can upload videos to TikTok.